Optimal management of malignant left-sided large bowel obstruction: do international guidelines agree? - Peter John Webster; Joanna Aldoori; Dermot Anthony Burke (World Journal of Emergency Surgery, 2019)
Abstract Background Approximately 20% of patients diagnosed with colorectal cancer will present with left-sided large bowel obstruction. The optimal management of this cohort of patients remains unclear. We aimed to review international guidelines to see if there was a consensus on the treatment of this surgical emergency. Methods The PubMed and Medline databases were searched for guidelines on the management of left-sided, malignant large bowel obstruction (MBO) between 2010 and 2018. Results Nineteen guidelines were identified spanning a range of continents. There was no clear consensus on the management of potentially resectable disease. Eight guidelines (42%) suggested primary surgery, two guidelines (11%) suggested stenting as a bridge to surgery and nine guidelines (47%) suggested surgery or stenting could be performed. Primary resection with or without anastomosis was the most frequently recommended procedure (n = 6 35%), but over a third of guidelines gave no operative recommendations. There was very limited detail on the stenting procedure and how long elective surgery should be deferred. In the palliative situation, there was general agreement that stents should be offered in preference to surgery. Conclusion International guidelines offer limited and contrasting recommendations on the management of left-sided MBO. There is a lack of high-quality evidence to support whether emergency surgery or stenting as a bridge to surgery is the optimal procedure in terms of morbidity, mortality and long-term oncological outcome.